Paciente masculino de 68 años con edema agudo de pulmón. - Salazar Quizhpe, Denisse Paulette (2021)
Acute lung edema is a disease caused by excess fluid in the lungs. Fluid collects in the many air sacs in the lungs and makes breathing difficult. In most cases, heart problems cause pulmonary edema. In most cases, heart problems cause pulmonary edema. Acute lung edema is caused by congestive heart failure. When the heart is unable to pump blood efficiently, it can be dammed up in the veins that carry blood through the lungs. The present clinical case is about a 68-year-old patient, who was admitted with dyspnea and precordial pain as the main symptoms, in addition to having a history of arterial hypertension. We must bear in mind that pulmonary edema is the excessive accumulation of extravascular fluid in the lung. The laboratory tests that were performed as chest x-rays and gasometry were the main diagnostic tests to verify or rule out another type of involvement at the pulmonary level, as for the gasometry it presented abnormal values of arterial gases. The patient is discharged shortly, which responded favorably to the treatment.